Glycosylation-dependent binding of galectin-8 to activated leukocyte cell adhesion molecule (ALCAM/CD166) promotes its surface segregation on breast cancer cells - Fernández, Marisa M.; Ferragut, Fátima; Cárdenas Delgado, Víctor M.; Bracalente, Candelaria; Bravo, Alicia I.; Cagnoni, Alejandro J.; Nuñez, Myriam; Morosi, Luciano G.; Quinta, Héctor R.; Espelt, María V.; Troncoso, María F.; Wolfenstein-Todel, Carlota; et al. (Biochimica et biophysica acta, 2016)
We previously demonstrated that the activated leukocyte cell adhesion molecule (ALCAM/CD166) can interact with galectin-8 (Gal-8) in endothelial cells. ALCAM is a member of the immunoglobulin superfamily that promotes homophilic and heterophilic cell–cell interactions. Gal-8 is a “tandem-repeat”-type galectin, known as a matricellular protein involved in cell adhesion. Here, we analyzed the physical interaction between both molecules in breast cancer cells and the functional relevance of this phenomenon. We performed binding assays by surface plasmon resonance to study the interaction between Gal-8 and the recombinant glycosylated ALCAM ectodomain or endogenous ALCAM from MDA-MB-231 breast cancer cells. We also analyzed the binding of ALCAM-silenced or control breast cancer cells to immobilized Gal-8 by SPR. In internalization assays, we evaluated the influence of Gal-8 on ALCAM surface localization. We showed that recombinant glycosylated ALCAM and endogenous ALCAM from breast carcinoma cells physically interacted with Gal-8 in a glycosylation-dependent fashion displaying a differential behavior compared to non-glycosylated ALCAM. Moreover, ALCAM-silenced breast cancer cells exhibited reduced binding to Gal-8 relative to control cells. Importantly, exogenously added Gal-8 provoked ALCAM segregation, probably trapping this adhesion molecule at the surface of breast cancer cells. Our data indicate that Gal-8 interacts with ALCAM at the surface of breast cancer cells through glycosylation-dependent mechanisms. A novel heterophilic interaction between ALCAM and Gal-8 is demonstrated here, suggesting its physiologic relevance in the biology of breast cancer cells. •Endogenous ALCAM from MDA-MB-231 breast cancer cells interacts with galectin-8.•Exogenous galectin-8 provokes ALCAM segregation and clustering at the cell surface.•ALCAM from MDA-MB-231 cells has high levels of α(2,6) sialylated glycans.•Galectin-8 and ALCAM are co-expressed in normal and malignant human breast tissues.